MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MELALUI PENDEKATAN KONTEKSTUAL - Junaidah (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2018)
This research aims to analyze the achievement and improvement of mathematical communication skill of SMP 1 Lembang students on functional and straight line equations, and examine the interactions between learning and KAM towards the improvement of students’ mathematical communication skills. This research is a quasi-experimental, with a Non-equivalent Control Group Design. The population of this study were whole eighth grade students at one of the junior high schools in Lembang city. The sample was determined using purposive sampling. The sample consisted of two classes, which were the experimental class that taught with contextual approaches, and the control class that received expository learning. The instrument used was a test of students' communication skills. The findings of this study were: (1) Achievement and improvement of mathematical communication skills of students who tutored by a contextual approach better than students who obtained regular learning both as a whole and KAM. (2) There is no interaction between learning and KAM (high, medium, low) towards the achievement of students' mathematical communication skills.